2005
DOI: 10.1007/s11183-005-0034-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nickel on growth, proliferation, and differentiation of root cells in Triticum aestivum seedlings

Abstract: The effect of 10 -6 and 10 -4 M NiSO 4 on cell growth, proliferation, and differentiation was studied over 48 h in seminal and lateral roots of five-day-old Triticum aestivum seedlings. 10 -6 M NiSO 4 did not significantly affect the root system, whereas 10 -4 M NiSO 4 inhibited its development. However, 10 -6 M NiSO 4 disturbed the contacts between the groups of closely related cells of the rhizodermis in the meristem. In the exodermis, an additional layer of cells was formed. At the nickel concentration of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 10 publications
4
14
0
Order By: Relevance
“…Our previous study showed that exposure of wheat seedlings to Ni led to an increase in root lignin content (Gajewska et al 2005). It can be suggested that a reduction in root growth in wheat exposed to excess Ni concentration might be associated with both decline in mitotic activity and restriction of cell elongation, which is in agreement with the recent findings of Demchenko et al (2005).…”
Section: Discussionsupporting
confidence: 89%
“…Our previous study showed that exposure of wheat seedlings to Ni led to an increase in root lignin content (Gajewska et al 2005). It can be suggested that a reduction in root growth in wheat exposed to excess Ni concentration might be associated with both decline in mitotic activity and restriction of cell elongation, which is in agreement with the recent findings of Demchenko et al (2005).…”
Section: Discussionsupporting
confidence: 89%
“…Proposals for causative mechanisms include (1) a general metabolic disorder (Mishra and Kar 1974;Baccouch et al 1998a;Murch et al 2003), (2) a decrease in cell wall plasticity (Pandolfini et al 1992), (3) impaired cell division and elongation (Robertson and Meakin 1980;Demchenko et al 2005), (4) disorganization of nuclear structures (Sresty and Rao 1999), (5) chromosomal aberrations (Liu et al 1995), and/or nutritional imbalances ). The injury produced by treatment with 1.5-5.00 mM NiCl 2 caused mitotic tip arrest of Vicia faba roots.…”
Section: Growth Attributesmentioning
confidence: 99%
“…Pandolfi ni et al [115] measured root lipid peroxidation already at 20 µM Ni 2ϩ in Triticum. Demchenko et al [116] observed inhibition of root development only at 100 µM Ni 2ϩ , when cell elongation decreased and later cell division stopped. But 1 µM Ni 2ϩ in the same experiment already led to subtle changes in the morphology of the rhizodermis, the relevance of which remained unclear.…”
Section: Inhibition Of Root Functionmentioning
confidence: 99%